LA ARQUITECTURA DEL CONVENTO FRANCISCANO DE SAN GINÉS DE LA JARA - Muñoz Clares, Manuel; García Blánquez, Luis A. (Imafronte, 2008)
In spite of the numerous literary and historical references that can be found regarding the Franciscan convent of San Ginés de la Jara, until now no clear establishment has been made of tlie different constructive stages the monument went through to acquire its modern day configuration. Based on news collected in a wide bibliographic index about the enclave, some unknown documents and the detailed visual inspection of the entire grounds, an arquitectural development proposal has been established for this interesting religious enclave, which, in a state of ruin and having been subjected to plundering, requires urgent intervention for its conservation.